The Routledge handbook of the bioarchaeology of climate and environmental change
1 online resource
Keywords: "This handbook examines human responses to climatic and environmental changes in the past, their impacts on disease patterns, nutritional status, migration, and interpersonal violence. Bioarchaeology-the study of archaeological human skeletons-provides direct evidence of the human experience of past climate and environmental changes and serves an important complement to paleoclimate, historical, and archaeological approaches to changes we may expect with global warming. Comprising 27 chapters from experts across a broad range of time periods and geographical regions, this book addresses hypotheses about how climate and environmental changes impact human health and well-being, factors that promote resilience, and circumstances that make migration or interpersonal violence a more likely outcome. The volume highlights the potential relevance of bioarchaeological analysis to contemporary challenges by organizing the chapters into a framework outlined by the United Nation's Sustainable Development Goals for 2030. Planning for a warmer world requires knowledge about humans as biological organisms with a deep connection to Earth's ecosystems balanced by an appreciation of how historical and socio-cultural circumstances, socio-economic inequality, degrees of urbanization, community mobility, and social institutions play a role in shaping long-term outcomes for human communities. Containing a wealth of nuanced perspectives about human-environmental relations, the handbook is key reading for students of environmental archaeology, bioarchaeology, and the history of disease. By providing a longer view of contemporary challenges, it may also interest readers in public health, public policy, and planning"--